IS THERE A DISTINCTIVE QUANTUM THEOLOGY?: with Mark Harris, "Quantum Theology beyond Copenhagen: Taking Fundamentalism Literally"; Shaun C. Henson, "What Makes a Quantum Physics Belief Believable? Many‐Worlds among Six Impossible Things before Breakfast"; Emily Qureshi‐Hurst, "The Many Worries of Many Worlds"; Elise Crull, "Interpretation Neutrality for Quantum Theology"; Wilson C. K. Poon and Tom C. B. McLeish, "Is There a Distinctive Quantum Theology?"; and Ernest L. Simmons, "The Entangled Trinity, Quantum Biology, and Deep Incarnation.". Issue 1 (15th February 2023) - Poon, Wilson C. K.; McLeish, Tom C. B.
Abstract: Quantum mechanics (QM) is a favorite area of physics to feature in "science and religion" discussions. We argue that this is at least partly because the arcane results of QM can be deployed to make big theological claims by the linguistic sleight of hand of "register switching"—sliding imperceptibly from technical into everyday language using the same vocabulary. We clarify the discussion by deploying the formal mapping of QM into classical statistical mechanics (CSM) via the mathematical device of "Wick rotation." This equivalence between QM and CSM suggests caution in claiming distinctiveness for quantum theologizing. After outlining two areas in which quantum insights nevertheless resonate with longstanding themes in theological reflection (hiddenness and visualizability), we suggest that both QM and CSM point to a theology of science in which scientists participate in the divine gaze on creation as imago Dei .